Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1024/0300-9831.73.6.439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Education on Food Consumption and Energy and Nutrient Intake in a Group of Pre-School Children from Madrid

Abstract: A study was conducted on the influence of maternal education level on food consumption, energy and nutrient intake, and dietary adequacy in 110 pre-school children from Madrid, Spain. With increasing maternal education, children consumed more sugar(p < 0.05), fruit (p < 0.05), and fish (p < 0.05). Snacking was more frequent with decreasing maternal education (p < 0.05). Though statistical significance was not reached, the consumption of pre-cooked foods was greater among children of mothers educated to a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…In all maternal education levels it was observed that there are problems of malnutrition both excess and deficit. Other authors observed that the educational level of parents is associated with the level of knowledge about health issues and accessibility to food they give their children [28,29]. Studies show that mothers who underestimate or overestimate the body weight of children could be a risk factor that increases the prevalence of malnutrition [30,31] similar to that situation observed in this work.…”
Section: Discussionsupporting
confidence: 77%
“…In all maternal education levels it was observed that there are problems of malnutrition both excess and deficit. Other authors observed that the educational level of parents is associated with the level of knowledge about health issues and accessibility to food they give their children [28,29]. Studies show that mothers who underestimate or overestimate the body weight of children could be a risk factor that increases the prevalence of malnutrition [30,31] similar to that situation observed in this work.…”
Section: Discussionsupporting
confidence: 77%
“…Not a single study on status in children was found. Table 1 gives an overview of data availability per country and study characteristics (2,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . Most data available were for adults, studying the relationship between vitamin C or Ca intake and education, occupation or income.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies on vitamin C intake in children showed lower mean intake in low-SES groups in comparison to high SES, except in Belgian boys (28) where the relative difference between SES groups was 12 %. In other studies where lower mean intake in low-SES groups in comparison to high SES was reported, relative differences ranged from 6 % in Turkish boys (18) up to 33 % for Spanish children (29) . Statistically significant differences between SES groups were found in studies from Finland (21) , Ireland (23) and Scotland (26) for adults and in the study from Spain (29) for children (P , 0?01).…”
Section: Calciummentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from studies that applied principal components analysis 16,17 or determined the degree of compliance with dietary recommendations 18,19 , other researchers have primarily paid attention to the socioeconomic status of the mother, particularly maternal education. For example, in a Spanish study investigating the association between level of maternal education and food consumption in pre-school children, consumption of added sugars, fruit and fish increased with increasing maternal education, while snacking was more frequent with decreasing maternal education 20 . Among several demographic characteristics examined in a cross-sectional survey in 2 -6-year-old children in England, high maternal education was positively associated with higher vegetable intake, but not with fruit intake 1 .…”
Section: Discussionmentioning
confidence: 99%